Short-circuit fault diagnosis of the DC-Link capacitor and its impact on an electrical drive system - Amine Mohamed Khelif; Azeddine Bendiabdellah; Bilal Djamal Eddine Cherif (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The reliability of a motor control based on a variable speed drive is an important issue for industrial applications. Most of these machines are inverter based induction motors and are used in specific and complex industrial installations. Unlike the induction motor, the feeding part is very delicate and sensitive to faults. In order to improve system performance, it is therefore very important for a researcher to know the impact of a fault on the whole of his drive system. This paper discusses the short-circuit fault of the DC-link capacitor of an inverter fed induction motor. The simulation results of this type of faults are presented and its impact on the behavior of the rectifier, the inverter as well as the induction motor analyzed and interpreted.